Nullity of the second order discrete problem with nonlocal multipoint boundary conditions - Paukštaitė, Gailė; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2015)
In this paper, we investigate several second order discrete problems with non-local multipoint boundary conditions and present obtained results about their nullity. The research was partially supported by the Research Council of Lithuania (grant No. MIP-047/ 2014).